Upaya Meningkatkan Kompetensi Profesional Guru SDN Andongsili Kecamatan Mojotengah Kabupaten Wonosobo melalui Coaching Model GROW Tahun Ajaran 2023/2024 - Suparna, Suparna (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Professional competence is one of the 4 important competencies that teachers must master. However, in reality, the professional competence of teachers is still lacking. This is the case for teachers at Andongsili primary school, Mojotengah sub-district, Wonosobo district. Teachers have not been able to improvise their own syllabus. Teachers still use the syllabus taken from the KKG results. Teachers who have implemented classroom action research usually only do it for their final assignment, while problems that occur in the classroom are usually only solved through discussions with the principal or colleagues. Teachers have not optimally utilized the development of technology and communication. For example, in making learning media and interactive modules, teachers have also not done reflection actions optimally after each lesson. This study aims to improve teachers' professional competence through GROW model coaching for teachers at SD Negeri Andongsili, Mojotengah District, Wonosobo Regency. This type of research is school action research (PTS), while the approach uses a quantitative approach. This research was conducted at Andongsili State Elementary School, Mojotengah District, Wonosobo Regency. The research subjects were teachers at SD Negeri Andongsili, Mojotengah District, Wonosobo Regency consisting of 7 teachers. The object of this research is teachers' professional competence. The research was conducted in two cycles consisting of three competencies each cycle, namely planning, implementation, and reflection. This research was conducted collaboratively between researchers and teachers at SD Negeri Andongsili, Mojotengah District, Wonosobo Regency. The data collection instruments used were test results and documentation. The results of this study indicate that the application of the GROW Coaching model can improve the professional competence of teachers at Andongsili State Elementary School, Mojotengah District, Wonosobo Regency The increase is shown from the average score of the pre tes and posttest to cycle II. Pre tes cycle I, the average score obtained was 74.28. The score increased in cycle II, which was 84.29. There was an increase of 10.01 points. In addition to the increase in pre tes, the pos tes score also increased. The pos tes score in cycle I obtained an average of 87.86, while cycle II increased to 92.86. In other words, there was an increase of 5 points. Because 100% of Andongsili teachers, Mojotengah District, Wonosobo Regency have managed to meet the KKM, this research is said to be successful. Keywords: Coaching, school action research, competence